Effect of low intensity ultra sound on bone regeneration and healing: a systematic review - Radha V; Sheeja S. VARGHESE (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Objective: Low Intensity Pulsed Ultra Sound (LIPUS) is found to have stimulatory effect on bone healing and regeneration. This review aimed to assess whether LIPUS enhances bone regeneration and healing in terms of efficiency in improving clinical, radiographic, histologic parameters or serum and tissue biomarkers. Methods: A comprehensive search based on PRISMA guidelines with pre-determined eligibility criteria was conducted to identify randomized controlled clinical trials evaluating effectiveness of Low intensity pulsed ultrasound in bone regeneration and healing. The title and abstract of the entries in all languages yielded from the PubMed, Google scholar and Cochrane library were screened. Results: 14 eligible Randomized controlled trials testing the effectiveness of LIPUS was evaluated. More heterogeneity was seen in the screened studies with respect to sample characteristics, type of bone and outcome measures. The studies that screened histological parameters state that LIPUS is significantly beneficial than control. In terms of time for radiographic union, most of the studies stated that LIPUS was more effective than control but numberof studies are very few. Whereas studies which evaluated parameters such as healing time and radiographic union were showing highly inconsistent results regarding effectiveness of LIPUS. Conclusion: This review cannot give a definitive conclusion that LIPUS is effective in bone healing with respect to clinical parameters but a positive influence on radiographical and histological parameters in bone healing and regeneration is promising to pursue future research.